A Rare Case of Intermittent Claudication Associated with Impaired Arterial Vasodilation - J. J. Posthuma; K. D. Reesink; M. Schütten; C. Ghossein; M. E. Spaanderman; H. ten Cate; G. Schep (Case Reports in Vascular Medicine)
Exercise-related intermittent claudication is marked by reduced blood flow to extremities caused by either stenosis or impaired vascular function. Although intermittent claudication is common in the elderly, it rarely occurs in the young and middle-aged individuals. Here, we report a case of exercise-related claudication in a 41-year-old woman, in the absence of overt vascular pathology. Using a series of imaging and functional tests, we established that her complaints were due to impaired arterial vasodilation, possibly due to a defect in nitrous oxide-mediated dilation. The symptoms were reversible upon administration of a calcium antagonist, showing reversibility of the vascular impairment. Identification of reversible vascular “stiffness” merits consideration in young and otherwise healthy subjects with claudication of unknown origin.